Gamification for Innovators and Entrepreneurs Using Games to Drive Innovation and Facilitate Learning - Bessant, John (De Gruyter, 2022)
This book provides a research-based overview of the use of games to facilitate learning in innovation/entrepreneurship and draws on work in several European institutions and well-known companies. Also, it provides a review of experiences in using games, a typology and a model for introducing games into course design. Examples include games specifically designed and developed within the project plus signpost links to an online library of games.